Gonadal Hormone Changes with Aging and Their Impact on Chronic Pain - Onella Athnaiel; Nicholas Davidson; Jaskaran Mangat; Ned F. Nasr; Nebojsa Nick Knezevic (Cells)
Chronic pain, pain that lasts beyond three months, is a common finding in the elderly. It is often due to musculoskeletal conditions but can be precipitated by other factors as well. While physiological systems decline with aging, chronic pain is influenced by changes in hormone profiles as men and women enter into andropause and menopause, respectively. Research on gonadal hormones is limited, especially when it comes to their relationship with chronic pain. Women tend to experience less pain with aging compared to their premenopausal years, and this is partially explained by the fact that estrogen enhances pain sensitivity and its decline during menopause decreases it. However, hormone replacement therapy (HRT) seems to increase pain tolerance post-menopause. There is some evidence that testosterone plays a protective factor in pain perception. Men on the other hand, have higher pain tolerance as testosterone is considered to be a protective factor. With aging and decreasing testosterone, older men tend to be less tolerant to pain. This paper explores how hormonal changes with aging impact pain perception in both men and women, highlighting several pain conditions influenced by hormones. Although research remains limited, the potential of HRT as a treatment for common pain conditions is examined.